Strategy to Determine The Level of Risk of Work Sites in The Construction Sector Using The Analytical Hierarchy Process (AHP) Method - Sunar, Sunar; Handani, Dhimas Widhi (Journal Research of Social Science, Economics, and Management, 2026)
The construction sector faces significant occupational safety challenges, with increasing accident rates necessitating strategic risk management approaches. This study aims to determine work site risk levels in the construction sector using the Analytical Hierarchy Process (AHP) method to optimize safety supervisor placement at PT. X, an international-scale construction fabrication company. The research identifies four main criteria affecting workplace risk: number of workers, critical activities, SIMOPS (Simultaneous Operations), and PTW (Permit to Work) issued, evaluated across seven alternative work locations. Data were collected through expert questionnaires involving HSE Managers, PTW Coordinators, and SIMOPS Facilitators. The AHP analysis revealed that critical activities constitute the most influential criterion with a weight of 47.1%, followed by SIMOPS (28.4%), PTW issued (17.1%), and number of workers (7.4%). Results indicate that NFQ Area 19 presents the highest risk level (0.407), while the Workshop area exhibits the lowest risk (0.024). The consistency ratio for all criteria remained below 0.1, confirming the reliability of the assessment. The findings were validated using Expert Choice software, demonstrating no significant calculation errors. This research provides a systematic framework for prioritizing safety supervision resources based on quantified risk levels, enabling more effective accident prevention strategies in construction environments.